2016
DOI: 10.5937/kgjmath1601047d
|View full text |Cite
|
Sign up to set email alerts
|

On parallel ruled surfaces in Galilean space

Abstract: Abstract. In this paper, we investigate the parallel surfaces of the ruled surfaces in Galilean space. There are three types of ruled surfaces in Galilean space. We derive the necessary conditions for each type of the ruled surfaces of the parallel surfaces to be ruled. Consequently, we construct some examples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 7 publications
0
21
0
Order By: Relevance
“…Substituting (10), (11), (12) and (13) into (7) completes the proof. [20] D. Sağlam and Ö. Kalkan, "Conjugate tangent vectors and asymptotic directions for surfaces at a constant distance from edge of regression on a surface in…”
Section: Kinematic Surfaces and K-kinematic Surfacesmentioning
confidence: 94%
See 1 more Smart Citation
“…Substituting (10), (11), (12) and (13) into (7) completes the proof. [20] D. Sağlam and Ö. Kalkan, "Conjugate tangent vectors and asymptotic directions for surfaces at a constant distance from edge of regression on a surface in…”
Section: Kinematic Surfaces and K-kinematic Surfacesmentioning
confidence: 94%
“…Mathematicians have written many articles and books by investigating surfaces as Euclidean and non-Euclidean. For these studies, one can read [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] . Eisenhart defined parallel surfaces and their some properties in his book [3].…”
Section: Introductionmentioning
confidence: 99%
“…In this part, we give a brief review of curves and surfaces in the Galilean space G 3 . For more details, one can see [12,[14][15][16]18].…”
Section: Preliminariesmentioning
confidence: 99%
“…The geometry of this non-Euclidean space was first studied intensively by Röschel [11]. In the last decade, this space was used by several researchers as an ambient space for the well-known Euclidean concepts (see [2,3,7,9,10] for more examples on special surfaces). The study of the surfaces in the Galilean 3-space can also be found in [1].…”
Section: Introductionmentioning
confidence: 99%